Clinical Sports Medicine - Schneider J (Dynamic Media Sales Verlag, 2019)
Background & Aim: Little is known about functional and motor deficits in male soccer players aged 9-13 and the impact they have on sports injuries and the prevention thereof. Hence, this study assesses functional and motor deficits in the aforementioned population and investigates the effects of an individualized training intervention on functional and motor deficits.Methods: This explorative, quasi-experimental study design allocated male soccer players (9-13 years) (n=48) into intervention group (n=23) and control group (n=25). Both groups performed the functional movement screen, toe touch test and weight-bearing lunge test pre-intervention and post-intervention. The intervention group performed a 12-week multimodal training intervention twice per week for 10-15 minutes. The total score of the functional movement screen and the results of the toe touch test and weight-bearing lunge test served as the outcome parameters.Results: We identified a variety of functional and motor deficits. All participants improved their total score of the functional movement screen (F(1)=32.27; p<0.001; peta=0.42), toe touch test (F(1)=10.48; p<0.01; peta=0.19) and weight-bearing lunge test (F(1)=8.46; p<0.01; peta=0.16). The intervention group showed higher improvements for the functional movement screen (F(1,46)=4.46; p<0.05; peta=0.09), toe touch test (F(1,46)=10.48; p<0.01; peta=0.19) and weight-bearing lunge test (F(1,46)=8.46; p<0.01; peta=0.16).Conclusion: A 12-week multimodal training intervention can effectively reduce functional and motor deficits identified in male soccer players aged 9-13 years and might serve as a helpful tool in injury prevention. KEY WORDS: Motor Deficits, Youth Soccer, Injury Prevention, Flexibility, Training Intervention